2017
DOI: 10.1080/13880209.2017.1362010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the hydroalcoholic extract of Rosa damascena on learning and memory in male rats consuming a high-fat diet

Abstract: Context: High-fat diet (HFD) can cause deficits in learning and memory through oxidative stress and increase Alzheimer disease risk. Rosa damascena Mill. (Rosaceae) extract possesses potent antioxidant properties. Objective: This study investigated the effects of the hydroalcoholic extracts of petals of R. damascena on learning and memory in male rats consuming an HFD. Materials and methods: Forty male Wistar rats (200–250 g) were randomly assigned to four groups: control, R. damascena extract, HFD and HFD + e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 70 publications
1
31
0
1
Order By: Relevance
“…Previous data suggest that MO contains high condensation of antioxidants (42)(43)(44)(45). The antioxidant activity of plants could be due to their phenolic compounds (27,46,47). MO has been shown…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous data suggest that MO contains high condensation of antioxidants (42)(43)(44)(45). The antioxidant activity of plants could be due to their phenolic compounds (27,46,47). MO has been shown…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, 30 seconds later the animal was delivered to the cage. After two minutes, the animal was retested and if it did not enter the dark chamber in 120 seconds, successful acquisition of a passive avoidance behavior was reported (27,28). The number of trials to the acquisition was reported as a measurement of learning (29,30).…”
Section: Passive Avoidance Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…The second test was performed at an interval of 24 hours, and the latency and the number of errors within 5 minutes for each mouse were recorded. 15…”
Section: Step-through Testmentioning
confidence: 99%
“…The step-through test is a standard method to assess shortterm or long-term memory of mice. 15 By using the stepthrough test, we examined the effects of SCA on the learning and memory in an AD model mice ( Figure 1). AD model mice were produced by Aβ 1-42 .…”
mentioning
confidence: 99%